KNOWLEDGE, ATTITUDES AND PRACTICES REGARDING DENGUE FEVER PREVENTION AND ASSOCIATED FACTORS AMONG STUDENTS AT HANOI UNIVERSITY PHYSICAL EDUCATION AND SPORTS, 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge, attitude, and practice (KAP) regarding dengue fever prevention and to analyze associated factors among students at Hanoi University of Physical Education and Sports in 2026.Research methods: A cross-sectional descriptive study was conducted among 216 students from October 2025 to February 2026. Data were collected using a structured questionnaire based on the KAP model through face-to-face interviews. Data were entered and analyzed using Stata version 18.0. Descriptive statistics and logistic regression analyses were applied to identify associated factors.Results: The proportions of students with adequate knowledge, attitude, and practice regarding dengue fever prevention were 71.3%, 60.2%, and 55.6%, respectively. Multivariable logistic regression analysis showed that place of residence and academic year were associated with knowledge, while knowledge was strongly associated with attitude. For practice, knowledge and attitude were significantly associated factors (p < 0.05).Conclusion: Students still exhibit certain limitations in knowledge and practice regarding dengue fever prevention. Health education and communication programs should be strengthened to improve awareness and promote dengue prevention behaviors among university students.
Keywords: Knowledge, attitude, practice, Dengue fever, students.